Analisis Theory Planned Behavior (TPB) terhadap Perilaku Ibu dalam Imunisasi Balita di Kecamatan Tenom Kabupaten Aceh Jaya - Hestia Sari Ernisa; Darmawan Darmawan; Firman Firdaus Saputra; Maiza Duana; Eva Flourentina Kusumawardani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Toddler immunization is an important effort to prevent infectious diseases and improve children’s health. However, immunization coverage in Tenom District is still low, at 25.6%. This study aims to analyze toddler immunization behavior based on the Theory Planned Behavior (TPB). The method used is quantitative with a cross-sectional survey design, involving 180 respondents from 18 villages selected by cluster random sampling. Inclusion criteria include mothers with toddlers aged 0-5 years, living in the Teunom health center area, being able to speak Indonesian, not using a caregiver, and willing to be respondents. Data were collected through interviews using questionnaires and direct observation of toddler KIA books. Data analysis using the chi-square test and multiple logistic regression. The results showed that bivariately there was a significant influence between attitude (OR = 2.128; P = 0.017), perceived behavioral control (OR = 2.577; P = 0.003), and intention (OR = 2.652; P = 0.002) on the type of immunization. However, subjective norms had no effect (OR = 1.706; P = 0.094). Multivariately, the intention variable became dominant with OR 2.241 and P = 0.019, indicating that respondents with bad intentions were twice as likely to not receive complete immunization. The conclusion of this study is that there is a relationship between attitude, perceived behavioral control and intention towards the type of immunization in toddlers. While there is no relationship between subjective norms and the type of immunization in toddlers.